Culture: A Journey Through Diversity in Language Learning - Dong, Rui (Transactions on Social Science, Education and Humanities Research, 2024)
Culture has an important role in language teaching. Students from different backgrounds come from different cultural environments and have their own unique understanding of language learning. Language is not only a concrete expression of culture, but culture can also be expressed through language, and the two are mutually unified, so there is an inseparable link between culture and language. The purpose of this study is to discuss the influence of culture on language teaching and learning, analyze the significance of culture, and the role of culture, and then compare and contrast the performance of Chinese and Western students in language learning in many aspects, and analyze the influence of cultural differences on language learning from both sides, and give some suggestions and measures. In the results of the study, language learners can see that culture is beneficial to language learning, and emphasizing culture can effectively promote language learning. At the same time, cultural differences can also bring some challenges, including cultural conflicts and communication difficulties, etc. In order to mitigate the effects of these challenges, educators need to take steps to improve the situation. Overall, the benefits of culture for language learning outweigh the drawbacks, and by understanding and responding to the challenges, cultures are well-positioned to meet the needs of learners and facilitate intercultural communication.